2022
DOI: 10.1021/acs.macromol.1c02573
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Design of Enhanced π–π Interaction and Decarboxylation Cross-Linking of Polyimide Membranes for Natural Gas Separation

Abstract: Conventional gas separation membranes made of glassy polymers often exhibit increased segmental motion and reduced selectivity when exposed to highpressure condensable gases. Decarboxylation cross-linking can effectively improve the plasticization resistance and gas permeability of polymer membranes, but this usually comes at the expense of the gas selectivity. In this work, enhanced π−π interactions and decarboxylation cross-linking are synergistically designed among polymer chains by introducing benzimidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 57 publications
1
53
0
Order By: Relevance
“…In the UV−vis absorption spectra of 6FDA-IPD and BPDA-IPD PHI membranes as shown in Figures 5c and 5d, the absorption peak at 312 and 369 nm are attributed to π−π interactions between aromatic nucleus of 6FDA-IPD and BPDA-IPD PHI. 32,33 The absorption peaks move to 322 and 373 nm by annealing at 280 °C for 24 h. The red-shift proves a promoted π−π transition between aromatic nucleus of 6FDA-IPD and BPDA-IPD PHI, which is probably attributed to the enhancement of the π−π interaction. From the above analysis, we can infer that π−π interactions are further enhanced after the annealing treatment.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the UV−vis absorption spectra of 6FDA-IPD and BPDA-IPD PHI membranes as shown in Figures 5c and 5d, the absorption peak at 312 and 369 nm are attributed to π−π interactions between aromatic nucleus of 6FDA-IPD and BPDA-IPD PHI. 32,33 The absorption peaks move to 322 and 373 nm by annealing at 280 °C for 24 h. The red-shift proves a promoted π−π transition between aromatic nucleus of 6FDA-IPD and BPDA-IPD PHI, which is probably attributed to the enhancement of the π−π interaction. From the above analysis, we can infer that π−π interactions are further enhanced after the annealing treatment.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…Because of its inherent interchain interaction, it shows high membrane density (1.27 g/mL) and denser chain packing than other glassy polymers. To further increase chain rigidity and decrease free volumes, Lin’s group reported the use of H 3 PO 4 and terephthaloyl chloride to cross-link PBI to improve its size-sieving ability, thereby increasing the H 2 /CO 2 selectivity by almost 100%. , In addition, H 2 /CO 2 selectivity of polyimides could be improved via diamine cross-linking to manipulate chain rigidity and chain-packing efficiency. Chung’s group reported that a polyimide (6FDA-durene) membrane could be cross-linked by various amines such as ethylenediamine (EDA), diethylenetriamine (DETA), diaminobutane (DAB) dendrimers, and other diamines, and H 2 /CO 2 selectivity increased by more than 260%. This approach involves the reaction of the imide ring of polyimide with a cross-linker molecule to produce a polymer network structure. , Their results showed that chemical cross-linking of polyimide membranes remains one of the most promising methods for improving H 2 enrichment. However, these methods mentioned above usually face several challenges: (1) only a few polymers with rigid structure that can be directly used to separate H 2 and CO 2 ; (2) the serious loss of permeability due to the denser chain packing after modification; (3) the destruction of the main chain of the polyimide caused by excessive reaction and the decrease of molecular weight of the polymer after cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane-based gas separation has significant advantages, such as no phase change in separation operation, low energy cost, and simple equipment demand [ 155 , 156 , 157 ]. For feasible gas separation processes, high selectivity and high permeability are the basic requirements of membranes.…”
Section: Application Of Pi-based Compositesmentioning
confidence: 99%
“…29,30 The carboxylate groups on DABA also provide additional cross-linking reactions, for instance, radical generation, condensation, vinyl polymerization, metal coordination, acetalization, and urethane formation. 18,[31][32][33][34][35][36][37][38] For the clickable cross-linking reaction, we substituted the carboxylate groups on 6FDD with allyl moieties and investigated the resulting systematic changes in the mechanical strength, gas transport behavior, and plasticization resistance of the cross-linked membranes after post-casting the thiol-ene reaction with select thiol cross-linkers. Our conceptual approach could be advanced by incorporating other thiol linkers or by functionalizing the allyl moieties further, thus outlining general design principles for membranes to be used for specific applications.…”
Section: Design System Applicationmentioning
confidence: 99%